Attack of the fluffy bunnies - Beaty, Andrea (Amulet Books, 2010)
At Camp Whatsitooya, twins Joules and Kevin and new friend Nelson face off against large, rabbit-like creatures from the Mallow Galaxy who thrive on sugar, but are not above hypnotizing and eating human campers.